STRATEGI DAKWAH DI ERA DIGITAL IKATAN DA’I INDONESIA - Arbi Kurniawan; Emi Puspita Dewi (Yonetim Jurnal, 2024)
The background to technological developments is that da'wah in the digital era must utilize new media effectively. The rise of global culture and society's dependence on the media shows the important role of the media in conveying da'wah. If not utilized properly, this can affect the morals and morals of the millennial generation who are looking for their identity. This research method uses a qualitative research method that goes directly into the field or Field Research, using a descriptive approach, data collection techniques through interviews, observation and documentation. The results of research in the implementation of digital era da'wah certainly did not run smoothly and were immediately accepted by mad'u. There are challenges or obstacles faced by the Indonesian Da'i Association of Prabumulih City, there is still a lack of human resources who are active in the use of technology or the use of tools used when making digital da'wah. In conclusion, da'wah in the digital era is very important because in this way the da'i at the Indonesian Da'i Association of Prabumulih City can maximize da'wah, not only in offline form, considering that the times are increasingly sophisticated, doing da'wah digitally is an opportunity for da'is to do da'wah.